2023
DOI: 10.3390/ani13182976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spirulina platensis Supplementation on Carcass Characteristics, Fatty Acid Profile, and Meat Quality of Omani Goats

Fahad Al-Yahyaey,
Waleed Al-Marzooqi,
Ihab Shaat
et al.

Abstract: In a 70-day study, 36 Jabbali and Sahrawi bucks, aged 11 months, were utilized to evaluate the effects of different levels of spirulina dietary supplement (SP) on carcass characteristics, fatty acid profile, and meat quality traits in Omani goat breeds. The goats were put into six groups of six bucks, each at random. The diet consisted of a conventional concentrate feed ration (CFR) without spirulina (CON), and the CFR diet supplemented with spirulina at the levels of 2 g/head daily (T1) and 4 g/head daily (T2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The high economic and environmental costs associated with the production and long-distance transportation of feedstuffs such as cereals and soybeans, mainly produced in North and South America, and their direct competition with human consumption, have important repercussions on the sustainability of food and livestock production [9,10]. Furthermore, the search for alternative, long-term, and low-cost protein and energy sources for use in farm animal diets has intensified, becoming a strategic objective after the COVID-19 pandemic [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high economic and environmental costs associated with the production and long-distance transportation of feedstuffs such as cereals and soybeans, mainly produced in North and South America, and their direct competition with human consumption, have important repercussions on the sustainability of food and livestock production [9,10]. Furthermore, the search for alternative, long-term, and low-cost protein and energy sources for use in farm animal diets has intensified, becoming a strategic objective after the COVID-19 pandemic [11].…”
Section: Introductionmentioning
confidence: 99%
“…has emerged as a potential cost-effective, sustainable, viable, and high-nutritional-value food resource for many animal species [7]. It has been reported that the direct intake of Spirulina can improve growth performance and meat quality in ruminants, chickens, pigs, and rabbits [7,11,23].…”
Section: Introductionmentioning
confidence: 99%